Expression and phosphorylation of the Listeria monocytogenes ActA protein in mammalian cells. - Brundage, R A (1993)
Movement of Listeria monocytogenes within infected eukaryotic cells provides a simple model system to study the mechanism of actin-based motility in nonmuscle cells. The actA gene of L. monocytogenes is required to induce the polymerization of host actin filaments [Kocks, C., Gouin, E., Tabouret, M., Berche, P., Ohayon, H. & Cossart, P. (1990) Cell 68, 521-531; Domann, E., Wehland, J., Rohde, M., Pistor, S., Hartl, M., Goebel, W., Leimeister-Wachter, M., Wuenscher, M. & Chakraborty, T. (1992) EMBO J. 11, 1981-1990]. In this study, an in-frame deletion mutation within the actA gene was constructed and introduced into the L. monocytogenes chromosome by allelic exchange. This mutation resulted in a decrease (3 orders of magnitude) in virulence for mice. In tissue culture cells, the actA mutant was absolutely defective for the nucleation of actin filaments and consequently was impaired in cell-to-cell spread. Antiserum raised to a synthetic peptide encompassing the proline-rich repeat (DFPPPPTDEEL) of ActA was used to characterize the expression of the ActA protein. The ActA protein derived from extracellular bacteria migrated as a 97-kDa polypeptide upon SDS/PAGE, whereas the protein from infected cells migrated as three distinct polypeptides, one that comigrated with the 97-kDa extracellular form and two slightly larger species. Treatment of infected cells with okadaic acid resulted in decreased amounts of all forms of ActA and the appearance of a larger species of ActA. Phosphatase treatment of ActA immunoprecipitated from intracellular bacteria resulted in conversion of the larger two species to the 97-kDa form. Labeling of infected cells with 32Pi followed by immunoprecipitation showed that the largest molecular form of ActA was phosphorylated. Taken together, these data indicate that ActA is phosphorylated during intracellular growth. The significance of the intracellular modification of ActA is not known, but we speculate that it may modulate the intracellular activity of ActA.